A rare case of persistent fetal intestinal hyperechogenicity - Answer - Paolo Figliolini; Martina Rossano; Fabiola Guerra; Giulia Di Pietro; Maria Antonietta Marcialis; Maria Cristina Pintus (Hygeia Press di Corridori Marinella, 2021)
In our case, the hyperechogenicity of the fetal intestine was observed for the first time during the 12th week sonography and was not resolved later. At the ultrasound checkup at 27 weeks, there was intestinal and gastric dilation; during the following one, at 29 weeks, a peritoneal effusion was also evident. The conditions of the fetus worsened rapidly, and the cardiotocographic trace showed a very reduced cardiac variability that required an urgent cesarean section. The abdominal ultrasound performed immediately after birth revealed corpuscolar abdominal free fluids. The bowel loops were dilated, with very thick walls, filled with corpuscle material. The child's clinical condition worsened rapidly. The oxygen saturation was at the lower limit even after the administration of Curosurf®. For this reason, it was not possible to transfer the patient to the Pediatric Surgery Department. So the surgeon performed a paracentesis in the Neonatal Intensive Care Unit (NICU), subtracting about 100 cc of hemorrhagic fluid. After a transitory improvement, the little girl died. The autopsy confirmed the presence of an intestinal volvulus with extensive hemorrhagic necrosis of the whole ileum, with dilated loops filled with hemorrhagic fluid, in the absence of intestinal malrotation.